193k views
4 votes
Number 2 please thank you!!

Number 2 please thank you!!-example-1

1 Answer

6 votes

Answer:

the inverse of a function takes the output of the actual function as the input and gives the input of the initial function as the output

here, we are given that when we input 23 in the inverse function of 'f', we get 3

this means that if we input 3 in the initial function, we will get 23 as the output

f(x) = x² - ax + 8

changing the input value to 3

f(3) = (3)² - 3a + 8

changing the output value to 23

23 = 9 - 3a + 8

3a = 17 - 23

3a = -6

a = -2

User Zoia
by
5.1k points